Height-nutrient Composition Relationship of Five Native Range Species - Al-ani, Tariq A.; Jawad, Maida (Indian Forester, 1974)
The nutrient distribution at various heights of five native range species was investigated. These included Artemisia herba-alba, Haloxylon salicornicum, Rhanterium epapposum, Achillea fragrantissima and Haloxylon articulatum. Generally, crude protein, crude fat and potassium were at highest levels in the terminal portion of the plants, gradually decreasing toward the plant base. The highest level of the crude fibre was found at the base then declined gradually towards the plants apex. The other nutrient components varied with various species. The results revealed that the upper plant portions are more nutritious than the lower portions. In addition, younger plants (30 cm high) seem to contribute better to animal nutrition than older plants (50 to 70 cm hight).